The use of Thinkercad tool and Scratch language to teach the programming fundamentals in Internet of Things (Research, Society and Development, 2021)
Over the last years, the Internet of Things (IoT) has been used in different fields of knowledge, such as industrial area, a health area and logistics, among many others. The enormous connectivity between devices and people is generating new solutions to a number of everyday problems. It is well known that, many devices are built, in addition to micro controlled systems, by sensors and/or actuators capable of reading external signals of the environment or even causing controlled changes, in order to generate movements and desired actions in this same environment. In this sense, the present study has evaluated the effectiveness of the Tinkercad tool, combined with the Scratch language, to teach students of bachelor’s courses of Computer Science, Information Systems and Technologies in Informatics, the main programming fundamentals associated with use of sensors in applications commonly found in the Internet of Things area. At the end of the classes, a questionnaire based on the Likert scale was used to assess different aspects of the student’s understanding of the use of Tinkercad and Scratch language in the developed exercises. A total of 174 students answered the questionnaire, and it was possible to verity that the aforementioned tool and the Scratch language actually offer a very favorable computational environment not only for the study of computational logic, but also for a better understanding of the functioning of some types of sensors normally applied in automation and particularly in the field of Internet of Things.